Assessment of TQM Practices as a Part of Supply Chain Management in Healthcare Institutions - TURKYILMAZ, Ali; BULAK, Muhammet Enis; ZAIM, Selim (International Journal of Supply Chain Management, 2015)
The aim of this study is to determine the critical factors of Total Quality Management (TQM) as Supply Chain Management (SCM) practices in the healthcare sector and to measure the effect of those factors on business performance of hospitals in Turkey. Performance of the hospitals was measured using subjective measures based on the hospitals administrators’ perception of how their organization performed relative to the competition. The technique of Partial Least Squares (PLS) analysis is employed to investigate the relationship between TQM practices and business performance. Analysis of the data from 50 hospitals revealed that TQM practices in the healthcare SCM influence financial performance indirectly by influencing non-financial performance. The results of the study provide strategic information about the importance of TQM factors such as supplier quality, service design, process management, employee relations, training, role of top management, and data and reporting for the successful healthcare SCM.